(untitled) - Upadhaya, J. L. (Darya Ganj, New Delhi, 2004)
Contents of material: Information retriaval. Libraries: The knowledge managers. Preserving digital information. Metadata approach in libraries. Information professionals. Access technology.
Keywords: Information storage and retrieval; Electronic data processing